1999
DOI: 10.1007/3-540-48892-8_22
|View full text |Cite
|
Sign up to set email alerts
|

The Nonhomomorphicity of Boolean Functions

Abstract: Abstract. We introduce the notion of nonhomomorphicity as an alternative criterion that forecasts nonlinear characteristics of a Boolean function. Although both nonhomomorphicity and nonlinearity reflect a "difference" between a Boolean function and all the affine functions, they are measured from different perspectives. We are interested in nonhomomorphicity due to several reasons that include (1) unlike other criteria, we have not only established tight lower and upper bounds on the nonhomomorphicity of a fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 3 publications
(4 reference statements)
0
11
0
Order By: Relevance
“…We start by analyzing the boolean function f (x) for a correlation property that we will use in the attack. A similar property is analyzed in [18] where they look at the nonhomomorphicity of functions. In this paper we identify the probability…”
Section: A Correlation Property Of Nonlinear Functionsmentioning
confidence: 99%
“…We start by analyzing the boolean function f (x) for a correlation property that we will use in the attack. A similar property is analyzed in [18] where they look at the nonhomomorphicity of functions. In this paper we identify the probability…”
Section: A Correlation Property Of Nonlinear Functionsmentioning
confidence: 99%
“…A generalization of the tests above was proposed by Zhang and Zheng in [14], where the authors defined the notion of (k + 1)-st order nonhomomorphicity of a function f as the probability P k (f ) of failing the test…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that for k odd, f is affine if and only if P k (f ) = 0; for k even, f is linear if and only if P k (f ) = 0; also, still for k even, f is affine if and only if P k (f ) ∈ {0, 1}. Furthermore, some bounds on P k (f ) with respect to d A (f ), for k odd, were given in [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The so-called plateaued functions in n variables (or r-plateaued functions) have been introduced in 1999 by Zheng and Zhang in [16,17] for 0 < r < n. They were intensively studied as good candidates for designing cryptographic functions in symmetric cryptography. For r ∈ {0, 1, 2}, r-plateaued functions have been actively studied and have attracted much attention due to their cryptographic, algebraic and combinatorial properties.…”
Section: Introductionmentioning
confidence: 99%